Examining the Impact of Green marketing on Consumer Engagement in Social Media Environment - Zhang, Siyu (2019)
Purpose: This research aims to explore the impact of green marketing in the social media environment on consumer engagement. To explore the impact, the researcher identified how green marketing influence the purchase intention on social media environment and the most crucial factor influence consumer green purchase intention. Moreover, evaluated the relationship between green purchase intention and consumer engagement. In addition, trying to figure out how consumers social media habit and the role of education/age in affecting consumers' purchase intention and consumer engagement. Design/methodology/approach: In this research, a conceptual model was established to test the relationship between green marketing and customer engagement in the social media environemnt and trying to understand the impact of green marketing on consumer behavior from the perspective of social media users. This research used an online questionnaire to collect social media users' data which meets the requirements, in addition, the researcher utilizes statistical tools - IBM SPSS to demonstrated research result and test the hypothesis Findings: research finding show that green brand awareness, ethical consumption habit, social image of corporation and identity have a positive impact on consumer green purchase intention. The statistic result shows that there is a correlation between consumer engagement and green purchase intention. And the difference in age of social media users could influence consumers' behavior such as subscribe the corporation official account, post green product or service feedback on social media, as well as purchase intention. However, education level did not show a significant difference in consumer engagement and purchase intention.